TELAAH RUKUN AL-TASYBIH SERTA REPRESENTASINYA DALAM AL-QUR’AN - Yura Marizka Sipahutar; M. Hafis Arafatha (Wahdatul Ulum Institute, 2026)
This article examines tasybih in the science of al-Balaghah. Tasybih is a branch of Bayan that explains a meaning and describes that meaning. This study aims to identify the definition of tasybih, the elements of tasybih, and examples of tasybih in the Qur’an. This article employs a literature review methodology using a descriptive analysis approach, which involves collecting data, organizing or clarifying it, and interpreting the findings. Tasybih is a branch of the science of Balaghah that deals with metaphors and the explanation of meanings. Tasybih serves as the first step in conveying a meaning and as a means to explain specific characteristics. Through tasybih, the conveyed meaning not only becomes clearer but also more powerful and possesses a high aesthetic value.